2022
DOI: 10.1002/admi.202102468
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible Flexible SERS Substrates Inspired by Bionic Micro‐Nano Hierarchical Structures of Rose Petals

Abstract: enlarge the signal of conventional Raman test, achieve trace detection, and even single-molecule detection. [4] Because of its unique fingerprint peak characteristics, non-destructive testing, fast response, and other advantages, [5,6] it is widely used in environmental monitoring, [7,8] food safety, [9][10][11] biomedicine, and other fields. [12][13][14] So far, there is no clear theoretical model that can explain the complex SERS phenomenon.However, electromagnetic enhancement (EM) and chemical enhancement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…[26,27] Recent studies have shown that some 3D-array substrates with high specific surface area gradually appear in the field of SERS detection. [29,30] In this paper, we designed an ordered micro-nano structure array with a layer of AgNPs growing on the surface for exosome surface protein detection (GPC1-Exos, LRG1-Exos, or CD9-Exos), which could provide more hot spots and a larger surface area. To verify whether the H-SERS substrate could provide a stronger SESR intensity, we characterized the detection performance of different substrates by detecting MBs @ exosomes @ Ag-MBA-CD9 detection probes (MEDP-CD9).…”
Section: Performance Characterization Of the Medp @ H-sers Substratementioning
confidence: 99%
“…[26,27] Recent studies have shown that some 3D-array substrates with high specific surface area gradually appear in the field of SERS detection. [29,30] In this paper, we designed an ordered micro-nano structure array with a layer of AgNPs growing on the surface for exosome surface protein detection (GPC1-Exos, LRG1-Exos, or CD9-Exos), which could provide more hot spots and a larger surface area. To verify whether the H-SERS substrate could provide a stronger SESR intensity, we characterized the detection performance of different substrates by detecting MBs @ exosomes @ Ag-MBA-CD9 detection probes (MEDP-CD9).…”
Section: Performance Characterization Of the Medp @ H-sers Substratementioning
confidence: 99%
“…For example, aircraft coatings based on shark skin resistance [6,[14][15][16], radar sonar based on bats [17], solar applications inspired by photosynthesis, bullet train heads based on kingfisher beaks [18,19], antifouling coatings based on frog skins [20], etc. Biomaterials have also been widely applied in SERS substrates due to their 3D periodic microstructures, such as butterfly wings, cicada wings, and rose petals [21][22][23]. The best case for the continuation, this study focuses on the surface structure of nepenthes.…”
Section: Introductionmentioning
confidence: 99%
“…To balance sensitivity and the sensing range, researchers have conducted many studies. Current methods primarily rely on the difference in the fracture toughness of sensitive conductive materials in different regions and forming cracks under different strains to achieve high sensitivity under a wide sensing range. For example, Liu et al took advantage of the self-pinning effect of the single-wall carbon nanotube solution to construct films of gradient thickness sensitive materials.…”
Section: Introductionmentioning
confidence: 99%